METAL OF IRON (Fe) AND MANGAN (Mn) FROM WASTE WATER COAL MINING WITH FITOREMEDIATION TECHNIQUES WITH USING FLOATING FERN (Salvinia natans), WATER LETTUCE (Pistia stratiotes) AND WATER-HYACINTH (Eichornia crassipes) - Mardalena, Mardalena; Faizal, Muhammad; Napoleon, A (BIOVALENTIA: Biological Research Journal, 2018)
Coal mining activities can cause problems from for environment, especially the mining with surface mining method producing acid mine water. To solve these problems, we need to restore the output water conditionbefore it flows into the public waters so it can meet the environmental quality standard in accordance with the prevailing laws and regulations. In this research, coal mining waste management was done by phytoremediation technique. This technique is the use water plants to give wastewater treatment. Water plants was used in this study was Kiambang (Salvinianatans), Apu wood plant (Pistiastratatiotes), and water hyacinth (Eichhorniacrassipers). This research observed the effect of time on the absorption of iron (Fe) and manganese (Mn) and the species of plant was used as phytoremediation agent. The results of the study discovered that the highest metal absorption in plants (phytoremediation agents) for 30 days for Mangan (Mn) parameter was water hyacinth (Eichhorniacrassipers) and the most absorption agent for iron was Kiambang (Salvinianatans) while based on measurement of metal content in the wastewater of mining, water hyacinth (Eichhorniacrassipers) was the most effective agent to absorb the iron (Fe) and Kiambang (Salvinianatans) absorbed Mangan (Mn) the most.